EFEKTIFITAS KOMBUCHA TEH BUNGA ROSELLA DALAM MENGHAMBAT PERTUMBUHAN BAKTERI ESHERICHIA COLI DAN SHIGELLA DYSENTERIAE UNTUK MENCEGAH TERJADINYA DIARE - Fatayati, Imma; Djohan, Herlinda; Roofiif, Sayyid Al (Jurnal Laboratorium Khatulistiwa, 2024)
One probiotic product is kombucha tea. Kombucha tea can be combined with rosella tea. Some of the bacteria that attack the digestive tract are Escherichia Coli and Shigella dysenteriae which can cause diarrhea. It has been suggested that probiotics can be used to prevent diarrhea. This research aims to determine whether there are probiotic benefits of Rosella flower kombucha fermented for 7 days and 14 days to prevent diarrhea. Review of the growth inhibitory power of Escherichia Coli and Shigella dysenteriae bacteria. This research is in the form of Quasi-experimental. The population of this study was rosella flower kombucha. The sample for this research was rosella flower kombucha with 7 days of fermentation and 14 days of fermentation. The number of repetitions for each treatment was 16 replications, with total replications was 62 replications. The results of this research showed that the inhibitory power of rosella flower kombucha against Shigella dysenteriae bacteria with an average fermentation time of 7 days was 11.31 mm (strong), for 14 days of fermentation the average was 24.72 mm (very strong). Meanwhile, the inhibitory power of rosella flower kombucha against E. Coli bacteria with a fermentation time of 7 days averaged 11.09 mm (strong), for 14-day fermentation, the average was 20.34 mm (very strong). This research concluded that the inhibitory power of rosella flower kombucha fermented for 7 days was in the strong category and 14 days in the very strong category for both the growth of Shigella dysentriae and `E. coli bacteria.